Factors of Maternal Influence on Low Birth Weight - Herwanto, Eko Setyo; Hudiyanto, Prima Sultan; Muhammad, Izbikavik (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Low birth weight (LBW) is classified by World Health Organization (WHO) as a weight at delivery of under 2500 g. LBW has now become a substantial public health concern worldwide, and it is connected to a variety of short and long term outcomes. The goal of this study is to identify maternal variables that impact the occurrence of low birth-weight infants. Material and Methods: The research used a cross-sectional study design with descriptive analysis, aiming to explain the characteristics and maternal risk factors that influence low birth weight over a period of 1 year at Soedomo Trenggalek Regional Hospital. Research subjects were women that delivered due to infants weight fewer than 2500 grams at Soedomo Trenggalek Regional Hospital from July 2022 to June 2023. Results: A sample of 105 patients was obtained. The mean age of the mothers were 29, pregnancies at age <20 years (n=6), age >35 years (n=19), gestational ages were at term (n=64), vaginal delivery (n=80), anemia (n=32), preeclampsia (n=16), Oligohydramnios (n=18), premature rupture of membranes (n=30), miscarriage or stillbirth (n=22). Conclusion:: Clinicians are expected to detect early risk factors or comorbid conditions in the mother and carry out appropriate and immediate management to prevent babies from being born with small birth weight.